(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2023)
Hibah is a type of property instrument used in Islam to manage the distribution of wealth among Muslims. It is a voluntary transfer of property during one’s lifetime to another person, be they an heir or non-heir. In its practice in Malaysia, several issues arise related to the implementation of hibah, most notably concerning its pillars, which require resolution by the Shariah Court. As an institution of justice in Muslim affairs, the Shariah Court is responsible for handling and deciding on hibah cases. This study examines the emerging issues that have been tried and decided by Shariah Court judges through selected law journal reports in Malaysia between 2014 and 2019. This study used library research by referring to hibah cases published in the selected law journals and analysed them using the thematic content analysis method. Thus, based on the analysis conducted, it was determined that the primary issue decided by the Shariah Court Judge is the pillars of hibah. Among them is the verification of hibah, that is, whether the hibah complies with its pillars or not. Keywords: Property, hibah, hibah cases, Muslim affairs, Shariah Court, Malaysia Full text: PDF